Liquid-Liquid Extraction Assisted Reverse phase HPLC Method for Quantitative Estimation of Dapagliflozin from Biological Matrix-Human Plasma: Development and Validation - Shirode, A. R.; Khanvilkar, V. V.; Chavan, P. S.; Tamboli, G. V.; Tyagi, C. K.; Chandekar, A. R. (Journal of Neonatal Surgery, 2025)
High performance liquid chromatography (HPLC) method was developed and validated for determination of Dapagliflozin in spiked human plasma using ornidazole as an internal standard (IS) for therapeutic monitoring. The resolution was achieved on Hemsil C18 column with mobile phase composed of Methanol : Double distilled water (80 : 20%) at flow rate 1ml/min. and detection wavelength was 236 nm. Sample preparation was carried out to separate Dapagliflozin from biological matrices by liquid-liquid extraction method. The developed method could give resolved peak of Dapagliflozin and Ornidazole at 5.2 and 3.2 min. respectively. The method was validated as per ICH M10 guidelines. The method was linear in range of 10 to 50 µg/ ml and it’s lower limit of quantitation and limit of quantitation were 10-50 µg/ ml respectively. The intra- and inter-day precision (%CV) were found to be in range of 0.77 to 7.20%, its accuracies were > 96% and recovery studies in range of 76.14 to 89.12%. Results of stability studies were found to be within specified range. The proposed method is characterized with highly sensitive, accurate, rapidity, as it consumes low volume of organic solvent in mobile phase and has high analysis throughput as its run time was short (~10 min).